(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Many Asian farmers are shifting from rice transplanting to direct seeding because the latter requires less labour, time, drudgery, and cultivation cost. Direct seeding is usually practiced in either wet or dry land preparation depending on water availability. The present study aimed at evaluating the potential of single and paired rows drill seeding patterns and five N management strategies on crop productivity, N use-efficiency, and apparent N balance. The experiment was laid out in a split plot design with two seeding patterns as main plots and five N treatments as subplots with three replications. Drill seeding did not affect grain yield, water, and N use-efficiencies and N balance. Grain yield increased with LCC-based N management with the lower N fertilizer input. Soil available N after 2 years of rice cropping was similar to the amount at the beginning indicating most of applied fertilizer N was lost. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14374 Bangladesh J. Agril. Res. 37(4): 559-571, December 2012